Clinical and economic constituents of the application of dexamethasone and tocilizumab in the therapy for severe conditions in patients with COVID-19 - O. V. Zhukova; A. L. Khokhlov (Фармакоэкономика)
Background. Severe forms of COVID-19 are associated with the development of a cytokine storm that is characterized by an increased secretion of anti-inflammatory cytokines. Thus, one of the leading strategies of treatment for patients with severe forms of COVID-19 is a decrease in the concentration of anti-inflammatory cytokines and inhibition of their effect on the organism.Objective: to perform a comparative analysis of clinical and economic constituents of the application of an IL-6 inhibitor tocilizumab and systemic glucocorticosteroid dexamethasone for the therapy of severe conditions in patients with COVID-19 based on the published data review.Material and methods. The authors analyzed the data obtained from PubMed/MEDLINE databases on the study dedicated to the application of tocilizumab and dexamethasone for the therapy of severe conditions in patients with COVID-19. A statistical evaluation of the influence of these drugs on the 28-day survival rate of patients with a severe form of COVID-19 was performed. The statistical tools included methods of the attribute-based statistic (attribute-based efficiency, relative efficiency (RE), populational attributive efficiency (PAE)). For the visualization of the clinical efficiency of the compared drugs, the authors applied beta-distribution. Markov’s model was used for modeling of the mortality rate. The modeling included the study of a hypothetical cohort of patients (1,000 patients with COVID-19). Besides, the authors evaluated the economic constitutive of the therapy with tocilizumab and dexamethasone. The cost-effectiveness analysis was performed.Results. The indication of dexamethasone statistically significantly increases the survival rate by 3.1% and tocilizumab – by 22.5%. RE was 1.04 (95% CI 0.040–2.042) for dexamethasone and 1.66 (95% CI 0.400–2.917) for tocilizumab. The lower border of 95% CI for both drugs was within the range of values <1, which was statistically significant. PAE for dexamethasone was 1.0% (95% CI –0.6–2.6), for tocilizumab – 16.5% (95% CI –0.7–33.7). Lower borders of 95% CI for both drugs ranged within negative values, which was not statistically significant. NNT (dexamethasone) was 32; NNT (tocilizumab) was 4. Markov’s modeling showed that the mortality rate among patients who received these drugs was 36 out of 1000 patients with COVID-19 for dexamethasone (initially distributed by the degree of severity according to the official statistical data) and 30 out of 1000 patients for tocilizumab, respectively. The cost of the treatment course with dexamethasone was 107.45 rub., tocilizumab – 78,827.20 rub. Clinical efficiency by the rate of cured patients obtained as a result of Markov’s modeling among patients with severe forms of COVID-19 for both drugs was comparable (0.964 for dexamethasone and 0.970 for tocilizumab) with slightly higher values for tocilizumab.Conclusion. Despite relatively comparable clinical efficiency of dexamethasone and tocilizumab and a significantly higher cost the later, it is not impossible to replace tocilizumab with dexamethasone because of a great number of side effects and potential inter-drug interactions during the treatment of severe forms of COVID-19. In particular, dexamethasone therapy should be performed with caution in patients with diabetes mellitus. Procurement planning should be made taking account the reserves of tocilizumab for the stabilization of patients with cytokine storm when dexamethasone application is not safe.